Muscle dysmorphia: what about transgender people?. Issue 1 (4th January 2022) - Amodeo, Anna Lisa; Esposito, Concetta; Antuoni, Sabrina; Saracco, Giovanni; Bacchini, Dario
Abstract: Muscle dysmorphia is characterised by a strong preoccupation with being lean and muscular, with negative psychological and social consequences. The condition mostly affects men, mainly because of sociocultural messages promoting hyper-muscular forms as ideal male figures. Relatively few studies have examined muscle dysmorphia in transgender people. Using a sample of 293 Italian adults, in this study we compared muscle dysmorphia symptoms (drive for size, appearance anxiety/avoidance and functional impairment) across 60 binary transgender (women and men whose gender identity did not conform to their biological sex), 217 cisgender (women and men whose biological sex aligns with their gender identity) and 16 non-binary people (those whose gender identity did not fall within the binary gender system). We also investigated the effect of the internalisation of body ideals on the development of muscle dysmorphia, analysing the moderating role of gender identity. Findings showed that i) transgender and cisgender men scored similarly higher on drive for size, ii) transgender men scored higher on appearance anxiety/avoidance, compared to other gender groups, iii) no differences were found in functional impairment. The effect of internalisation of body ideals on drive for size was stronger in cisgender men. Findings signal the importance of investigating risk factors for muscle dysmorphia in transgender people.